2003
DOI: 10.1097/00006676-200311000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Somatostatin Receptor Subtype 2 Inhibits Insulin Secretion in the Isolated Perfused Human Pancreas

Abstract: We demonstrated that the SSTR 2 agonist and octreotide significantly suppressed insulin secretion. Furthermore, even during the immunoneutralization of endogenous intrapancreatic somatostatin, the SSTR 2 agonist was able to reverse the effect of somatostatin immunoneutralization by suppressing insulin secretion. These results demonstrate that activation of SSTR 2 suppresses insulin secretion in the isolated perfused human pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…Although our findings do not entirely match the expression pattern of SSTR they are in agreement with two previous studies on perfused human pancreas, describing SSTR2 as an inhibitor of insulin secretion (15,28). However, in these studies less SSTR2-selective agonists have been tested.…”
Section: Discussionsupporting
confidence: 65%
“…Although our findings do not entirely match the expression pattern of SSTR they are in agreement with two previous studies on perfused human pancreas, describing SSTR2 as an inhibitor of insulin secretion (15,28). However, in these studies less SSTR2-selective agonists have been tested.…”
Section: Discussionsupporting
confidence: 65%
“…Although the effects of the SSTR3 agonist did not reach overall statistical significance, a clear and reversible inhibition of exocytosis was obtained in some ␣-cells, which is compatible with heterogeneous receptor expression. A similar order of potency for SSTR1, -2, and -5 agonists (i.e., SSTR2 Ͼ SSTR5 Ͼ SSTR1 for insulin, SSTR2 Ͼ SSTR1 Ͼ SSTR5 for glucagon) was observed in hormone secretion measurements from isolated human islets (9,37), but an SSTR3 agonist was found to be ineffective in these studies. It is likely that the same SSTR3 agonist employed in the present study was also used in the studies of Brunicardi et al (9) and Singh et al (37) (based on its K i values for SSTR isoforms), but it is unclear which concentrations were tested in those studies.…”
Section: Discussionsupporting
confidence: 64%
“…A similar order of potency for SSTR1, -2, and -5 agonists (i.e., SSTR2 Ͼ SSTR5 Ͼ SSTR1 for insulin, SSTR2 Ͼ SSTR1 Ͼ SSTR5 for glucagon) was observed in hormone secretion measurements from isolated human islets (9,37), but an SSTR3 agonist was found to be ineffective in these studies. It is likely that the same SSTR3 agonist employed in the present study was also used in the studies of Brunicardi et al (9) and Singh et al (37) (based on its K i values for SSTR isoforms), but it is unclear which concentrations were tested in those studies. The low affinity of the compound for SSTR2 makes it unlikely that the effects observed here were mediated by a different receptor isoform.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We used a modified in-house sliding scale equation for bolus insulin administration, which takes into account initial blood glucose levels and a target glucose concentration of~5.0 mmol/l, in an attempt to modestly elevate relative insulin levels during exercise. However, insulin concentrations were not measured during this protocol and it is unclear if the SSTR2a promoted increased insulin secretion, which has been reported for cultured human islets [44]. Nonetheless, Yue et al [26] found no change in systemic insulin levels in rats with STZ-induced diabetes given SSTR2a, likely because SSTR5 is the main receptor isoform in beta cells in rats [25].…”
Section: Discussionmentioning
confidence: 83%